Metabolically-inactive glucagon-like peptide-1(9–36)amide confers selective protective actions against post-myocardial infarction remodelling. Issue 1 (December 2016) - Robinson, Emma; Tate, Mitchel; Lockhart, Samuel; McPeake, Claire; O'Neill, Karla; Edgar, Kevin; Calderwood, Danielle; Green, Brian; McDermott, Barbara; Grieve, David
ABSTRACT Background Glucagon-like peptide-1 (GLP-1) therapies are routinely used for glycaemic control in diabetes and their emerging cardiovascular actions have been a major recent research focus. In addition to GLP-1 receptor activation, the metabolically-inactive breakdown product, GLP-1(9–36)amide, also appears to exert notable cardiovascular effects, including protection against acute cardiac ischaemia. Here, we specifically studied the influence of GLP-1(9–36)amide on chronic post-myocardial infarction (MI) remodelling, which is a major driver of heart failure progression. Methods Adult female C57BL/6 J mice were subjected to permanent coronary artery ligation or sham surgery prior to continuous infusion with GLP-1(9–36)amide or vehicle control for 4 weeks. Results Infarct size was similar between groups with no effect of GLP-1(9–36)amide on MI-induced cardiac hypertrophy, although modest reduction of in vitro phenylephrine-induced H9c2 cardiomyoblast hypertrophy was observed. Whilst echocardiographic systolic dysfunction post-MI remained unchanged, diastolic dysfunction (decreased mitral valve E/A ratio, increased E wave deceleration rate) was improved by GLP-1(9–36)amide treatment. This was associated with modulation of genes related to extracellular matrix turnover (MMP-2, MMP-9, TIMP-2), although interstitial fibrosis and pro-fibrotic gene expression were unaltered by GLP-1(9–36)amide. Cardiac macrophage infiltration was also reduced by GLP-1(9–36)amide together with pro-inflammatory cytokine expression (IL-1β, IL-6, MCP-1), whilst in vitro studies using RAW264.7 macrophages revealed global potentiation of basal pro-inflammatory and tissue protective cytokines (e.g. IL-1β, TNF-α, IL-10, Fizz1) in the presence of GLP-1(9–36)amide versus exendin-4. Conclusions These data suggest that GLP-1(9–36)amide confers selective protection against post-MI remodelling via preferential preservation of diastolic function, most likely due to modulation of infiltrating macrophages, indicating that this often overlooked GLP-1 breakdown product may exert significant actions in this setting which should be considered in the context of GLP-1 therapy in patients with cardiovascular disease.